Change in the structures of significance in organizations of small producers. An understanding from institutional theory (Encuentros, 2020)
The institutional theoretical perspective that promises to overcome the comprehensive narrowness of instrumental rationalism, guided the approach to the phenomenon of change in organizations of small producers of the primary link of the dairy chain in Colombia, on the occasion of a public policy instrument that sought to alleviate the impacts of the commercial opening of the sector. This article deals with the change in the structures of significance, understood as social construct, in small producers in the department of Boyacá. A qualitative interpretive study was carried out whose finding is specified in that the institutional arrangements on which the state support mechanism was based, did not achieve the construction of meaning among the beneficiary subjects, and consequently, the expected changes did not occur .